Differences in the individual behavior as related to the preference of use of espaces of broiler breeders as a function of the thermal environment - Pereira, Danilo Florentino; Curto, Fábio Penna Firme; Nääs, Irenilza de Alencar (Brazilian Journal of Veterinary Research and Animal Science, 2006)
The study of animal behavior has been efficient in identifying welfare of housed broilers. Bird preference related to housing and thermal environment has been studied in several countries. However the ability of homeotherms to adept in hostile ambient results in distinct individual needs, and leads to heterogeneity in the flock and inevitable loss in production. To reduce these losses it is necessary to know the individual needs of group of birds in order to group the similar individuals together. This research had the objective to demonstrate the feasibility of use of telemetry and electronic identification for monitoring the individual preferences and specific behavior of female broiler breeders in reduced and distorted scale model. The results showed that the use of electronic identification associated to telemetry were efficient in studying the movement of birds. Through the observational analyses of obtained frequency distribution graphs it was possible to identify the individuals that better adapted to specific housing thermal environment.